Active load and loss allocation in transmission line via improved cuckoo search optimization technique / Nur Atiqah Abdul Rahman - Abdul Rahman, Nur Atiqah (2014)
The introduction of deregulation in transmission system has given the opportunity for the end user to choose the supplier. This has brought the importance of active load and loss allocation in transmission line. Due to the nonlinear character of power flow, it is crucial to allocate the losses and active load. Thus, this research has proposed a novel technique to allocate both active load and losses in transmission line using a newly developed Improved Cuckoo Search (ICS) Optimization Technique. In addition, a new objective function has also been proposed in this research to improve the accuracy of the power allocation. The active load and transmission loss allocation have been treated as an optimization problem. In this research, IEEE 5-Bus, Ward- Hale 6-Bus, IEEE 30-Bus and also IEEE 57- Bus systems are used as test systems and a comparative study is conducted with Cuckoo Search (CS) technique and also Genetic Algorithm (GA) technique. In addition, the proposed method with the new objective function is also tested in line outage and load increase conditions. The results are compared in terms of accuracy of the allocation, computational time and also the consistency. From the results and comparative study, the proposed new technique offers an accurate allocation of power among the market participants. Hence, they will be charged fairly for their transmission cost as required in a deregulated power system.